The Sociology of Gender Roles in Traditional and Modern Bugis Families - Baharuddin, Baharuddin; Malik, Abdul; Rizqullah, Riyan (Journal Social Humanity Perspective, 2025)
In this paper, the author analyses the role of gender in traditional and modern Bugis family focusing on how cultural continuity and societal transformation intersect to create a state of familial management and the broader implications on society. Using a qualitative methodology, the study examines the historical process by which traditional Bugis families granted authority, responsibility and symbolic meaning to males through a patriarchal framework that was supported by cultural values, including siri (honor) and pacce (compassion). It was the role of women in this arrangement to be involved in the domestic and cultural continuity, but they did not have the decision making authority as their male counterparts. Modern Bugis families, especially in urban settings, on the contrary are showing a slow transition into gender elasticity, propelled by education, economic engagement and contact with external ideas of equality. Women are also more empowered in terms of financial decisions, careers and are also more active in the domain of leadership roles, whereas men are more engaged in domestic roles. Continuity however still exists because the cultural values of malebbi (modesty) and warani (courage) still influences gender ideals, the conflict with alternative conceptions of masculinity and femininity is still an intergenerational conflict. The evidence shows us that tradition has not been completely abandoned, but it is renegotiated; the traditional values are rebuilt in the new realities of society. These observations have relevance in the area of management studies since cultural legitimacy in the process of organizational change underscores the need to ensure that long-term change does not come through undermining tradition but by redefining it to fit into the new socio-economic environment. Therefore, the study fits in the wider gender, management, and cultural adaptation debates, and the case of the Bugis can serve as an illustrative case of the need to balance between heritage and modernization.